Foetal instrumental extractions (IE) at the maternity at Nabil Choucair Health Center (Senegal) from 2005 to 2016: epidemio-clinical and prognostic aspects - Gassama, Omar; Faye, Ndeye Astou; Diouf, Abdoul Aziz; Niang, Mouhamadou Mansour; Mbaye, Magatte; Ndour, Daouda; Dieme, Marie Edouard Faye; Thiam, Ousmane; Ndiaye, Abdou; Diouf, Alassane; Moreau, Jean Charles (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The main objective was to take stock of practices on instrumental extractions at the maternity of Nabil Choucair Health Center. Methods: This was a prospective, descriptive study from 1 January 2005 to 31 April 2016. The collection was carried out through the data sheet completed on the basis of an analysis of files, the delivery register and the anaesthesia register of the operating room. The data was entered using the Sphinx software version 5 and the data analysis performed by Epi info version 3.5. Results: 240 instrumental extraction cases were compiled, and their frequency was 0.4%. The mean age of patients was 24.8 years. Obstetric vacuum was the most commonly used instrument (66.4%) and an episiotomy was performed in 73.6%. Maternal complications were dominated by simple perineal tears (6.2%). Conclusions: Instrumental extractions should be rehabilitated in our maternity facilities to combat the outbreak of the caesarean section. Instrumental extractions indications and techniques should be controlled to avoid complications